Granger Causality Between Gross Domestic Product and Economic Sectors in Developing Countries: A Panel Co-integration Approach - Siami-Namini, Sima (International Journal of Economics and Financial Issues, 2017)
The purpose of this article is to explore the causal relationship between GDP and economic sectors including agricultural, industrial, and services growth and oil price using a balanced panel data of 62 developing countries observed over the period of 1990 to 2014. The results of multiple regressions show that industrial and services value-added share of GDP and oil price are the positive influencing factor of the GDP of developing countries. In contrast, agricultural value-added share of GDP identifies as a negative influencing factor of the GDP. To examine the Granger causal relationship between variables, the vector error correction model (VECM) and Wald tests statistics are applied. The findings show a long run relationship of Granger causality between variables and show a short run bi-directional Granger causality between GDP and agriculture and service and oil price and a short run unidirectional Granger-causality from industry to GDP. Keywords: Economic sectors, Oil price, Developing countries, Panel Co-integration, Granger-causality JEL Classifications: O1; O13; O14; C33